PEMODELAN DISTRIBUSI KUCING TANDANG (Prionailurus planiceps) DI KAWASAN RESTORASI EKOSISTEM RIAU DI SEMENANJUNG KAMPAR, RIAU - Fikri, Husnul; Novarino, Wilson; Rizaldi, .; Iqbal, Muhammad (Universitas Pakuan, 2024)
The flat-headed cat is categorized as a threatened species by the International Union for the Conservation of Nature (IUCN). As the beginning of a conservation strategy for species that are difficult to find in nature, knowing the actual distribution of species in the field is important. Maximum entropy (Maxent) has emerged as an accurate prediction method for species distribution. This study aimed to analyze the distribution of flat-headed cats and important variables affecting their distribution in the Riau Ecosystem Restoration (RER) area on the Kampar Peninsula, Riau. A total of 6 finding points and 17 environmental variables were used in the modeling of this study. The Area Under Curve (AUC) value of the flat-headed cats was 0.890, indicating that the model performance was categorized as satisfactory. High habitat suitability was predicted ≥ 19% or (24,736.83 ha) of the total area. Environmental variables that influenced their distribution were distance from trails, distance from canals, and distance from rivers. The high suitability of the flat-headed cats’ habitat in the PT GCN concession is potentially along the Sangar River. In the PT SMN concession in the central and northwestern parts of the concession. PT TBOT concession is in areas adjacent to the Turip and Serkap Rivers. Although not detected in previous surveys, PT GAN has the potential to detect the presence of flat-headed cats in the eastern part and adjacent to the Serkap River.